Question
upstudy study bank question image url

QUESTION 5 Given: \( f(x)=\frac{4}{x-3}+2 \) and \( g(x)=x+2 \) \( 5.1 \quad \) Write down the equations of the asymptotes of \( f \). \( 5.2 \quad \) Determine the \( x \)-intercept of \( f \). 5.3 \( \begin{array}{ll}\text { Determine the } y \text {-intercept of } f . \\ 5.4 & \begin{array}{l}\text { Sketch the graphs of } f \text { and } g \text { on the same system of axes. Show clearly ALL the } \\ \text { intercepts with the axes and any asymptotes. } \\ 5.5\end{array} \quad \text { Calculate the } x \text {-coordinates of the points of intersection of } f \text { and } g \text {. } \\ 5.6 & \text { If } x<3, \text { determine the values of } x \text { for which } \frac{4}{x-3}+2
Ask by Parry Martinez. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**5.1: Asymptotes of \( f(x) \)** - Vertical Asymptote: \( x = 3 \) - Horizontal Asymptote: \( y = 2 \) **5.2: \( x \)-intercept of \( f(x) \)** \( (1, 0) \) **5.3: \( y \)-intercept of \( f(x) \)** \( \left(0, \frac{2}{3}\right) \) **5.4: Graphs of \( f(x) \) and \( g(x) \)** - **Asymptotes**: Vertical at \( x = 3 \) and Horizontal at \( y = 2 \) - **Intercepts**: - \( f(x) \): \( (1, 0) \) and \( \left(0, \frac{2}{3}\right) \) - \( g(x) \): \( (0, 2) \) and \( (-2, 0) \) **5.5: Points of Intersection** \( x = 4 \) and \( x = -1 \) **5.6: Values of \( x \) where \( \frac{4}{x-3} + 2 < x + 2 \) for \( x < 3 \)** \( -1 < x < 3 \) **5.7: Coordinates of \( Q \)** To find \( Q \), solve \( \frac{4}{x-3} + 2 = x - 1 \): \[ \frac{4}{x-3} = x - 3 \] Multiply both sides by \( x - 3 \): \[ 4 = (x - 3)^2 \] \[ x - 3 = \pm 2 \] So, \( x = 5 \) or \( x = 1 \). Since \( P \) is at \( x = 1 \), \( Q \) is at \( x = 5 \). Thus, \( Q(5, 4) \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Mind Expander

The function \( f(x) = \frac{4}{x-3} + 2 \) has a vertical asymptote where the denominator is zero, which occurs at \( x = 3 \). This means that as \( x \) approaches 3, \( f(x) \) will increase or decrease without bound. Additionally, there is a horizontal asymptote at \( y = 2 \) because as \( x \) approaches positive or negative infinity, the term \( \frac{4}{x-3} \) approaches 0. To find the \( x \)-intercept of \( f \), set \( f(x) = 0 \): \[ 0 = \frac{4}{x-3} + 2 \] Solving gives \[ \frac{4}{x-3} = -2 \implies 4 = -2(x - 3) \implies x - 3 = -2 \implies x = 1 \] So, the \( x \)-intercept is at \( (1, 0) \). For the \( y \)-intercept, set \( x = 0 \): \[ f(0) = \frac{4}{0-3} + 2 = -\frac{4}{3} + 2 = \frac{2}{3} \] Thus, the \( y \)-intercept is \( (0, \frac{2}{3}) \). To sketch the graphs, plot the asymptotes at \( x = 3 \) (dashed vertical line) and \( y = 2 \) (dashed horizontal line). The graph of \( f \) approaches these lines, and the intercepts show where it crosses the axes. The line \( g(x) = x + 2 \) is a straight line with a \( y \)-intercept of 2 and a slope of 1, coming in from below the horizontal asymptote at \( y = 2 \). To find \( x \)-coordinates of the intersection of \( f(x) \) and \( g(x) \), set the equations equal: \[ \frac{4}{x-3} + 2 = x + 2 \] This simplifies to \( \frac{4}{x-3} = x \); cross-multiplying yields \( 4 = x(x-3) \). Rearranging gives: \[ x^2 - 3x - 4 = 0 \] Factoring leads to \( (x-4)(x+1) = 0 \), so \( x = 4 \) or \( x = -1 \). Next, for \( \frac{4}{x-3} + 2 < x + 2 \): Subtracting 2 gives \( \frac{4}{x-3} < x \), resulting in \( 4 < x(x-3) \), or \( 0 < x^2 - 3x - 4 \). Solving the quadratic \( x^2 - 3x - 4 = 0 \) leads again to \( (x-4)(x+1) = 0 \). Thus, the intervals where the inequality holds are \( x < -1 \) or \( x > 4 \) (keeping \( x < 3 \)). So, the valid solution is \( x < -1 \). For the point \( Q \) where the line \( y = x - 1 \) cuts \( f \), substitute \( x - 1 \) into \( f \). Setting equations equal gives: \[ \frac{4}{x-3} + 2 = x - 1 \] Solving this yields \( x = 5 \) for \( P \). Substituting into the line equation \( y \) gives \( Q(5, 4) \).

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy